TI_GERICHTE 15.2006.113 vom 2. Januar 2007 , Pignoramento di salario. Tredicesima mensilità. Assistenza giudiziaria - TI Tribunale d'appello (2007)
Pignoramento di salario. Tredicesima mensilità. Assistenza giudiziaria